Method for preparing high-performance magnet based on spark plasma rapid sintering
By performing presintering and two-stage annealing heat treatment before rapid SPS sintering, the problems of uneven diffusion of heavy rare earth elements and reduced magnet orientation during the sintering process are solved, and the preparation of high-performance NdFeB magnets is achieved.
Patent Information
- Application Number
- CN202510079603.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-25
AI Technical Summary
During the sintering process, the existing NdFeB magnets cause uneven interdiffusion of heavy rare earth elements due to high temperature and high pressure, resulting in deterioration of magnetic properties and waste of heavy rare earth resources. At the same time, the greater pressure in the SPS process will lead to a decrease in the orientation of the magnet.
By pre-sintering before SPS rapid sintering, grain orientation is fixed, and SPS rapid sintering is performed at lower temperatures and shorter time, combined with two-stage annealing heat treatment, the shell thickness of the core-shell structure and the orientation of the magnet are controlled.
It effectively inhibits the interdiffusion of heavy rare earth elements, improves the uniformity and squareness of the magnet structure, improves the orientation and residual magnetism of the magnet, saves heavy rare earth resources, and achieves uniform and controllable shell thickness.
Smart Images

Figure BDA0005248132850000071 
Figure BDA0005248132850000081 
Figure HDA0005248132860000011
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a homogeneous high-performance NdFeB magnet based on SPS rapid sintering, and belongs to the technical field of rare earth permanent magnet materials. Background Art
[0002] Rare earth permanent magnet materials are essential functional materials in the field of high-tech in today's society. They are closely related to people's lives and are widely used in communications, audio and video, machinery, medical treatment, instrumentation, computers, home appliances, transportation, energy, aerospace, national defense and other fields. Among them, Sm-Co and Nd-Fe-B rare earth permanent magnet materials with high magnetic energy product and high coercivity will effectively promote the development of modern science and technology and information industry towards integration, miniaturization and intelligence, thus providing great convenience for human production and life.
[0003] Nd 2 Fe 14 NdFeB permanent magnet material with B phase as the main phase is the magnetic material with the highest comprehensive performance at this stage. It is the third generation of permanent magnets after samarium cobalt permanent magnets. Because of its high magnetic properties, it is used in many fields and is an indispensable and important magnetic material. In order to obtain higher magnetic properties, the diffusion of heavy rare earth elements such as Tb and Dy through grain boundaries has become a mainstream process. However, in the NdFeB magnet treated by surface grain boundary diffusion, the heavy rare earth elements diffuse in a gradient manner and are enriched on the surface of the magnet to form an inverse core-shell structure, which on the one hand causes a waste of heavy rare earth resources and cannot be evenly diffused to the center, resulting in the deterioration of the squareness and magnetic properties of the diffused magnet; and the magnets doped with heavy rare earth element powder in NdFeB powder to optimize the composition after sintering heat treatment can form a relatively uniform core-shell structure, but due to the high sintering temperature (over 1000°C) and long sintering time (over 2 hours), the heavy rare earth diffuses violently, which limits the improvement of magnetic properties and low utilization of heavy rare earth. Therefore, the use of spark plasma rapid sintering (SPS) technology with lower densification temperature and shorter densification time to densify grain boundary doped magnetic powder can effectively inhibit the diffusion process of heavy rare earths. Combining heat treatment process to obtain a more uniform core-shell structure and thus obtain high-performance NdFeB magnets has become a key research direction. However, the higher pressure in the SPS process will cause a significant decrease in the orientation of the magnet, resulting in a decrease in the remanence of the magnet. Therefore, how to improve the orientation of SPS magnets is also an urgent problem to be solved.
[0004] Therefore, those skilled in the art are committed to developing a technology for preparing homogeneous high-performance NdFeB magnets based on SPS rapid sintering, so that the NdFeB magnets prepared based on SPS have higher core-shell uniformity and performance. Summary of the invention
[0005] In order to prepare the above magnets, the present invention provides a technology for preparing homogeneous high-performance NdFeB magnets based on SPS rapid sintering. The sintering temperature and time of preparing sintered magnets are reduced and shortened through the new process of the present invention, which can effectively inhibit abnormal grain growth, and the lower sintering temperature and shorter sintering time can effectively inhibit the mutual diffusion of heavy rare earths, and control the shell thickness of the core-shell structure to be lower than that of traditional diffusion magnets. At the same time, pre-sintering can keep the orientation of the magnet unchanged during the SPS process, and finally obtain a high-performance magnet with a uniform core-shell structure and a uniform and controllable shell thickness.
[0006] The first object of the present invention is to provide a method for preparing a NdFeB magnet, comprising the following steps: mixing heavy rare earth element powder or heavy rare earth alloy powder with original NdFeB magnet powder and pre-sintering at a relatively low temperature; then performing SPS rapid sintering; and finally performing two-stage annealing heat treatment to obtain a magnet;
[0007] The pre-sintering temperature is 700-900°C and the duration is 0.5-3h;
[0008] The SPS rapid sintering has a sintering temperature of 800-950°C, a pressure of 50-80MPa, and a pressure holding time of 10-20min;
[0009] The two-stage annealing heat treatment has a first-stage temperature of 800-900° C. for 3-5 hours, and a second-stage temperature of 400-500° C. for 3-5 hours.
[0010] The present invention adopts heavy rare earth element or heavy rare earth alloy to dope NdFeB magnet, such as Dy element, Tb element, DyM alloy, TbM alloy, REDyM alloy, RETbM alloy (where RE=Pr, Nd, M=Cu, Al, Co, Ga, Fe, Zr), fixes grain orientation by pre-sintering, and then adopts low sintering temperature 800-950℃ for SPS rapid sintering, so that magnet is rapidly densified, and heavy rare earth does not interdiffusion occurs, forming a thinner core-shell structure with uniform shell thickness (the shell thickness of the basic core-shell structure of the material prepared once by the present invention is uniform); finally, by annealing treatment, the grain structure can be optimized and the grain defects can be reduced. The method shortens the sintering time, reduces the sintering temperature, can effectively inhibit the interdiffusion of heavy rare earth elements, improves the uniformity and squareness of the magnet structure, and can regulate the shell thickness.
[0011] As the most preferred embodiment of the present invention, the preparation method comprises the following steps:
[0012] (1) mixing heavy rare earth single substance powder or heavy rare earth alloy powder into original NdFeB magnet powder to form mixed powder; the particle size of the heavy rare earth single substance powder or heavy rare earth alloy powder is 50nm-3μm (the particle size of the original NdFeB magnet powder is larger than that of the heavy rare earth single substance powder or heavy rare earth alloy powder), and the mass ratio of the heavy rare earth single substance powder or heavy rare earth alloy powder to the original NdFeB magnet powder is 0.5-2%;
[0013] (2) Mixing heavy rare earth element powder or heavy rare earth alloy powder with original NdFeB magnet powder in a certain proportion and then pre-sintering, the pre-sintering temperature is 800-900℃, and the time is 2-3h; then SPS rapid sintering is carried out, the SPS rapid sintering temperature is 850-950℃, the pressure is 50-60MPa, and the pressure holding time is 10-20min; finally, two-stage annealing heat treatment is carried out, the first stage temperature is 850-900℃, the time is 3-5h, and the second stage temperature is 400-500℃, and the time is 3-5h, to obtain a high-performance magnet with a core-shell structure, the core is a NdFeB magnet, and the shell is a diffusion phase.
[0014] The heavy rare earth element is selected from Dy or Tb.
[0015] The shell thickness obtained by the above method is uniform and ranges from 10 nm to 1 μm.
[0016] The second object of the present invention is to provide a neodymium iron boron magnet prepared according to the above preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention adopts the SPS rapid sintering process to prepare sintered magnets, which reduces the sintering temperature and shortens the sintering time, can effectively inhibit the mutual diffusion of heavy rare earth elements, improve the uniformity and squareness of the magnet structure, and can regulate the shell thickness;
[0019] In the SPS process alone, due to the low density of the pressed green body, the orientation of the magnet will be destroyed under the action of pressure, resulting in a decrease in the orientation degree of the final magnet. Therefore, pre-sintering is added before SPS to increase the density of the pressed green body and fix the orientation, thereby improving the orientation degree and remanence of the SPS magnet.
[0020] (2) The present invention adopts the SPS rapid sintering process to prepare sintered magnets, which improves the effective utilization rate of Dy or Tb and saves heavy rare earth resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the structure of diffused magnet, doped magnet and SPS magnet. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0023] If no specific techniques or conditions are specified in the examples, all are carried out according to conventional methods or the techniques or conditions described in the literature in the field, or according to the product instructions. If no manufacturer is specified for the reagents and instruments used, all are conventional products that can be purchased through regular channels.
[0024] Comparative Example 1
[0025] According to the original magnet powder Nd 31 FeB, prepare A component quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder.
[0026] In a glove box, the A component was jet-milled and oriented in an inert gas atmosphere to obtain a green body. The green body was vacuum-packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering. After being kept at a sintering temperature of 1050°C for 3 hours, argon gas was passed through the furnace for cooling, and then a primary heat treatment was performed at 900°C for 3 hours, and then a secondary heat treatment was performed at 480°C for 4 hours to obtain magnet D. 1 .
[0027] The prepared magnet D 1 Perform the BH test and the results are as follows:
[0028] Original magnet D 1 :B r =14.38kG, H cj =13.33kOe, (BH) max =48.79MGOe, H k / H cj =96.8%, I (006) / I (105) =1.46. (006) / I (105) It represents the peak intensity ratio of the diffraction peak of the crystal (006) plane to the diffraction peak of the (105) plane. It is used as a standard to measure the orientation degree of the magnet. Generally, the orientation degree of sintered magnets is greater than 1.3.
[0029] Comparative Example 2
[0030] According to the original magnet powder Nd 31FeB, prepare component A quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder; Dy single substance nanopowder B is prepared by nano furnace, and after passing through a 100 mesh sieve, a fine powder of 100-200nm is obtained.
[0031] In a glove box, the fine powders of components A and B were mixed at a mass ratio of 95.5:0.5. After being fully mixed, they were oriented and formed in an inert gas protective atmosphere to obtain a green body. The green body was vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering. After being kept at a sintering temperature of 1090°C for 3 hours, argon gas was passed through the air for cooling, and then a primary heat treatment was performed at 900°C for 3 hours, and then a secondary heat treatment was performed at 495°C for 4 hours to obtain magnet D. 2 .
[0032] The prepared magnet D 2 Perform the BH test and the results are as follows:
[0033] Doped magnet D 2 :B r =14.20kG, H cj =15.27kOe, (BH) max =47.27MGOe, H k / H cj =95.3%, I (006) / I (105) =1.35, shell thickness 4μm, corresponding to Figure 1 (c) in .
[0034] Comparative Example 3
[0035] According to the original magnet powder Nd 31 FeB, prepare component A quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder; Dy single substance nanopowder B is prepared by nano furnace, and after passing through a 100 mesh sieve, a fine powder of 100-200nm is obtained.
[0036] In a glove box, the A component was jet-milled and oriented in an inert gas atmosphere to obtain a green body. The green body was vacuum-packed and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering. After sintering at 1050°C for 3 hours, argon gas was passed through the furnace for cooling, and then a primary heat treatment was performed at 900°C for 4 hours, and then a secondary heat treatment was performed at 480°C for 3 hours to obtain magnet D. 1 Then, the B component fine powder was sprayed at a weight gain ratio of 0.5%, and then the primary diffusion was carried out at 900℃ for 6h, and then the secondary diffusion was carried out at 480℃ for 3h to obtain magnet D. 3 .
[0037] The prepared magnet D 3 Perform the BH test and the results are as follows:
[0038] Diffusion magnet D 3 :B r =14.16kG, H cj =19.78kOe, (BH) max =47.26MGOe, H k / H cj =89.4%, I (006) / I (105) =1.35, the surface layer forms an inverse core-shell structure, the Dy-containing region is 7 μm in the central region, the shell thickness at a depth of 100 μm is 2.5 μm, and no core-shell structure is formed at a depth of 500 μm, corresponding to Figure 1 (a) in .
[0039] Example 1
[0040] According to the original magnet powder Nd 31 FeB, prepare A component quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder.
[0041] In a glove box, component A is oriented and formed under an inert gas protective atmosphere to obtain a green body. The green body is vacuum packaged and cold isostatically pressed. After grinding in the glove box, the green body fits the SPS mold. Spark plasma sintering is performed at 850°C, the pressure is 50MPa, and the pressure holding time is 10min. Then, a primary heat treatment is performed at 850°C for 3h, and then a secondary heat treatment is performed at 440°C for 3h to obtain magnet E. 1 .
[0042] The prepared magnet E 1 Perform the BH test and the results are as follows:
[0043] SPS Sintered Magnet E 1 :B r =13.25kG, H cj =12.12kOe, (BH) max =41.47MGOe,
[0044] H k / H cj =95.0%, I (006) / I (105) =0.94.
[0045] Example 2
[0046] According to the original magnet powder Nd 31FeB, prepare A component quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder.
[0047] In a glove box, the A component was jet-milled and oriented in an inert gas atmosphere to obtain a green body. The green body was vacuum-packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for pre-sintering. After the pre-sintering temperature was kept at 850°C for 2 hours, argon gas was passed through the air cooling, and then the pre-sintered magnet was polished by a grinder to fit the SPS mold. Spark plasma sintering was performed at 900°C, the pressure was 55MPa, and the pressure holding time was 15min. Then, a primary heat treatment was performed at 875°C for 4h, and then a secondary heat treatment was performed at 460°C for 4h to obtain magnet E. 4 .
[0048] The prepared magnet E 2 Perform the BH test and the results are as follows:
[0049] SPS Sintered Magnet E 2 :B r =14.36kG, H cj =13.62kOe, (BH) max =48.54MGOe,
[0050] H k / H cj =95.4%, I (006) / I (105) =1.52.
[0051] Example 3
[0052] According to the original magnet powder Nd 31 FeB, prepare component A quick-condensed thin strip, hydrogen crushing and dehydrogenation to obtain coarse crushed magnetic powder, and then air flow grinding to obtain 3μm fine powder; Dy single substance nanopowder B is prepared by nano furnace, and after passing through a 100 mesh sieve, a fine powder of 100-200nm is obtained.
[0053] In a glove box, the jet-milled powders of components A and B were mixed in a mass ratio of 95.5:0.5. After being fully mixed, they were oriented and formed in an inert gas protective atmosphere to obtain a green body. The green body was vacuum-packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for pre-sintering. After being kept at a pre-sintering temperature of 900°C for 3 hours, argon gas was passed through the air cooling, and then the pre-sintered magnet was polished by a grinder to fit the SPS mold, and spark plasma sintering was performed at 950°C with a pressure of 60MPa and a holding time of 20min. Then, a primary heat treatment was performed at 900°C for 5h, and then a secondary heat treatment was performed at 480°C for 5h to obtain magnet E. 5 .
[0054] The prepared magnet E 3 Perform the BH test and the results are as follows:
[0055] SPS Sintered Magnet E 3 :B r =14.28kG, H cj =21.36kOe, (BH) max =48.10MGOe,
[0056] H k / H cj =95.6%, I (006) / I (105) =1.54, shell thickness 0.1μm; corresponding Figure 1 Middle (b).
[0057] The comparison results of the remanence, coercive force, maximum magnetic energy product and squareness of each magnet in the above comparative examples and embodiments are shown in Table 1.
[0058] Table 1 Performance of each magnet in comparative examples and embodiments
[0059]
[0060]
[0061] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing high-performance magnets based on spark plasma rapid sintering, characterized in that: The following steps are involved: A heavy rare earth element powder or a heavy rare earth alloy powder, such as Dy element, Tb element, DyM alloy, TbM alloy, REDyM alloy, RETbM alloy (where RE = Pr, Nd, M = Cu, Al, Co, Ga, Fe, Zr), is mixed with the original NdFeB magnet powder to form a mixed powder and pre-sintered at a relatively low temperature; then SPS rapid sintering is performed; and finally a two-stage annealing heat treatment is performed to obtain a high-performance magnet with a core-shell structure, wherein the core is a NdFeB magnet and the shell is a diffusion phase; The pre-sintering temperature is 700-900°C and the duration is 0.5-3h; The SPS rapid sintering has a sintering temperature of 800-950°C, a pressure of 50-80MPa, and a pressure holding time of 10-20min; The two-stage annealing heat treatment has a first-stage temperature of 800-900° C. for 3-5 hours, and a second-stage temperature of 400-500° C. for 3-5 hours.
2. The preparation method according to claim 1, characterized in that: The particle size of the heavy rare earth single substance powder or heavy rare earth alloy powder is 50nm-3μm.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the heavy rare earth single substance powder or / and the heavy rare earth alloy powder to the original NdFeB magnet powder is 0.5-2%.
4. The preparation method according to claim 1, characterized in that: The particle size of the original NdFeB magnet powder is larger than the particle size of the heavy rare earth single substance powder or / and the heavy rare earth alloy powder.
5. The preparation method according to claim 1, characterized in that: The heavy rare earth element is selected from Dy or Tb.
6. The preparation method according to claim 1, characterized in that: The pre-sintering temperature is 800-900℃, and the duration is 2-3h; then SPS rapid sintering is carried out, the SPS rapid sintering temperature is 850-950℃, the pressure is 50-60MPa, and the pressure holding time is 10-20min; finally, a two-stage annealing heat treatment is carried out, the first stage temperature is 850-900℃, the duration is 3-5h, and the second stage temperature is 400-500℃, and the duration is 3-5h.
7. The preparation method according to claim 1, characterized in that: The shell thickness is between 10nm and 1μm, and the squareness is greater than 95%.
8. A high performance magnet prepared according to the method according to any one of claims 1 to 7.